The role of AI-powered chatbots in enhancing second language acquisition: An empirical investigation of conversational AI assistants - Taeza, Jordan (Edelweiss Applied Science and Technology, 2025)
This study explores the role of AI-powered chatbots in enhancing second language acquisition (SLA), focusing on speaking proficiency, learner engagement, and confidence. A mixed-methods, quasi-experimental design was employed involving 60 intermediate ESL learners divided into a chatbot-assisted experimental group and a control group using traditional practice. Over six weeks, the experimental group engaged in structured interactions with a conversational AI chatbot offering real-time feedback. Pre- and post-tests, engagement surveys, and interviews were used for data collection. Findings revealed that the chatbot group showed significantly higher gains in speaking proficiency and greater improvements in willingness to communicate and self-confidence. Qualitative feedback highlighted increased practice, reduced anxiety, and high learner motivation, though limitations such as repetitive responses and limited cultural understanding were noted. The study concludes that AI chatbots can serve as effective supplemental tools in SLA, especially for enhancing oral skills and learner autonomy. Practical implications suggest integrating chatbots into language curricula for additional speaking practice, particularly in contexts with limited teacher availability. Educators are advised to blend chatbot use with guided instruction and monitor chatbot feedback quality to ensure pedagogical alignment.